2020
DOI: 10.1002/pchj.407
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics as a common denominator for moral and commercial judgments

Abstract: Using fMRI, a core evaluation mechanism was found for aesthetic judgments with add-on neural activities for moral and commercial judgments. We propose that aesthetic evaluations serve as a basic core mechanism implicitly for moral and commercial judgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The political abuse of its suggestive power is discussed as well (Vogel, 2009). The similarity between aesthetic perception and other cognitive processes has also been picked up by recent neuroimaging studies, indicating a common brain machinery (Avram et al, 2013; Tsukiura & Cabeza, 2011; Wang et al, in press). In this sense, the cognitive and neural machinery for aesthetic perception and other parts of perception and cognition may be intertwined.…”
Section: Proto‐aesthetic Perceptionmentioning
confidence: 84%
“…The political abuse of its suggestive power is discussed as well (Vogel, 2009). The similarity between aesthetic perception and other cognitive processes has also been picked up by recent neuroimaging studies, indicating a common brain machinery (Avram et al, 2013; Tsukiura & Cabeza, 2011; Wang et al, in press). In this sense, the cognitive and neural machinery for aesthetic perception and other parts of perception and cognition may be intertwined.…”
Section: Proto‐aesthetic Perceptionmentioning
confidence: 84%
“…Another study has already shown that there is a connection between the aesthetic assessment of beauty, moral, and economic evaluation. Beauty can be a component for moral goodness or commercial conviction (X. Wang et al, 2021). The effect of aesthetic qualities on moral goodness and commercial persuasiveness can be combined, especially in modern media formats.…”
Section: Beauty In Ethics and Aestheticsmentioning
confidence: 99%
“…Beauty can be a component for moral goodness or commercial conviction (X. Wang et al, 2021). The effect of aesthetic qualities on moral goodness and commercial persuasiveness can be combined, especially in modern media formats.…”
Section: Beauty In Ethics and Aestheticsmentioning
confidence: 99%
“…Behavioral studies in “neuroaesthetics” and the identification of underlying neural mechanisms have also led to theoretical reflections about anthropological universals and cultural specifics (Bao et al, 2016), about the general concept of complementarity as a generative principle in aesthetic appreciations (Bao et al, 2017a), or even aesthetics as a common denominator in different kinds of judgment (Wang et al, 2020). Thus, research in this interdisciplinary field of neuroaesthetics with its different empirical approaches and theoretical reflections contributes to better understanding cognitive mechanisms and their neural basis with respect to spatial characteristics and temporal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…As aesthetic judgment might have a surprisingly fundamental role in various judgments (Wang et al, 2020), it is conceivable to relate it to a relatively low level in the hierarchy of cognitive functions. More specifically, the aesthetic preference for the left perspective might be deeply rooted in the context of a basic perceptual bias; facial perception was found to be viewpoint‐dependent (Ewbank et al, 2008; Fang et al, 2007), with three‐quarter faces yielding better recognition over other perspectives (Krouse, 1981; Laeng & Rouw, 2001; Troje & Bülthoff, 1996), and the left view having a higher recognition rate than the right view (Arnold et al, 2013; Kowatari et al, 2004; Siéroff, 2001; Yamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%